2018
DOI: 10.35536/ljb.2018.v6.i2.a6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Service Quality, Customer Loyalty and Customer Satisfaction

Abstract: This study examined the influence of service quality on customer loyalty, and aimed to determine if this relationship was mediated by customer satisfaction. Data were gathered from customers of eight banks in Pakistan through an adapted self-administered questionnaire. Respondents were selected using convenience sampling. The distributed questionnaire was based on a modified SERVQUAL model.479 complete survey responses were returned out of a total of 700 distributed. The completed questionnaires were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
2
7
0
7
Order By: Relevance
“…Lastly, the result showed that trust has a mediating role in the relationship between open-book management and customer satisfaction. However, this result is consistent with the study's results (Kalia et al, 2021;Rehman et al, 2020;Zamry and Nayan , 2020;Al-Taii, Ismael and Khudhur , 2020;Mahmood, Rana and Kanwal , 2018;Yanik, 2018;Bricci, Fragata and Antunes, 2016;Nikzad and Maryam 2012;Alkhamis , 2018;Gul , 2014), Where trust had a partially mediating impact on the relationship between open-book management and customer satisfaction. This result can be supported by clarifying that trust has an important role in strengthening the relationship between open-book management and customer satisfaction, as through training, empowering, and delegating employees, the trust factor can be enhanced and thus leads to satisfying the needs and desires of customers because workers within the organization have been motivated in a way automatic.…”
Section: Al Haraisa Y E (2022)supporting
confidence: 88%
See 1 more Smart Citation
“…Lastly, the result showed that trust has a mediating role in the relationship between open-book management and customer satisfaction. However, this result is consistent with the study's results (Kalia et al, 2021;Rehman et al, 2020;Zamry and Nayan , 2020;Al-Taii, Ismael and Khudhur , 2020;Mahmood, Rana and Kanwal , 2018;Yanik, 2018;Bricci, Fragata and Antunes, 2016;Nikzad and Maryam 2012;Alkhamis , 2018;Gul , 2014), Where trust had a partially mediating impact on the relationship between open-book management and customer satisfaction. This result can be supported by clarifying that trust has an important role in strengthening the relationship between open-book management and customer satisfaction, as through training, empowering, and delegating employees, the trust factor can be enhanced and thus leads to satisfying the needs and desires of customers because workers within the organization have been motivated in a way automatic.…”
Section: Al Haraisa Y E (2022)supporting
confidence: 88%
“…Furthermore, Al-Taii, Ismael and Khudhur (2020) pointed out that there is a significant effect of open-book management on organizational agility Mahmood, Rana and Kanwal (2018). showed that customer satisfaction plays a mediating role in the relationship between service quality and customer loyalty Yanik(2018).…”
mentioning
confidence: 99%
“…Seperti kondisi fisik perusahaan, merupakan aspek yang secara kasat mata yang dipertimbangkan oleh konsumen tentang apakah mereka akan mengembangkan asosiasi jangka panjang dan melakukan retensi untuk menggunakan produk dan layanan pada perusahaan tersebut lagi (Zineldin, 2005). Juga, dalam teori diskonfirmasi dinyatakan bahwa kesesuaian harapan seseorang atas kondisi kualitas pelayanan aktual yang dipersepsikan dengan harapan-harapan seseorang akan mengarah pada perasaan senang dan timbulnya kesetiaan untuk kembali menggunakan layanan tersebut (Oliver dalam Mahmood, Tauheed Rana, and Kanwal 2018).…”
Section: Pengaruh Kualitas Pelayanan Terhadap Loyalitas Penumpangunclassified
“…Berbagai penelitian, seperti penelitian juga menyatakan temuannya bahwa kualitas pelayanan menjadi penentu loyalitas penumpang pada industri penerbangan di Nigeria (Ganiyu, 2016); kualitas pelayanan memiliki pengaruh terhadap loyalitas penumpang pada industri penerbangan di Pakistan rute ke Malaysia (Ali et al, 2021); kualitas pelayanan, seperti keamanan dan keandalan menjadi salah satu faktor yang mendorong munculnya loyalitas seseorang dalam menggunakan layanan transportasi ride-hailing di Kota Kuching, Malaysia (Ha et al, 2019); kualitas layanan seperti keselamatan penumpang, kenyamanan, kompetensi pengemudi, kebersihan kendaraan berpengaruh positif dan signifikan pada perusahaan angkutan umum (Etuk et al, 2021); kualitas layanan memiliki pengaruh signifikan dan positif pada perbankan di Pakistan (Mahmood et al, 2018); kualitas layanan menjadi aspek yang berpengaruh signifikan pada loyalitas penumpang pada transportasi publik di Tehran selama masa pandemi COVID-19 (Esmailpour et al, 2022); daya tanggap, jaminan, dan empati menjadi aspek dalam kualitas pelayanan yang memengaruhi loyalitas penumpang Trans Padang rute Pasar Raya -Lubuk Buaya (Wicaksono & Trinanda, 2020), serta; kualitas layanan memberi dampak signifikan terhadap kepuasan penumpang pada layanan dua penerbangan di Pakistan, yakni PIA dan Air Blue (Hussain et al, 2022).…”
Section: Pengaruh Kualitas Pelayanan Terhadap Loyalitas Penumpangunclassified
“…Todos estos resultados cuentan con un nivel de significancia menor a 5% por lo tanto, los porcentajes presentados anteriormente son significativos para la investigación. 1.9 Relación entre la calidad de servicio, la satisfacción y la lealtad del consumidor El análisis de la relación entre las tres variables mencionadas se ha encontrado en diversos estudios, el común entre ellos es que se realizaron en países en proceso de desarrollo Mittal et al, 2016; Khan repotenciación de calidad de servicio para implementar altos estándares de satisfacción y fidelización del cliente, generando de esa forma el éxito en una empresa.Con respecto a las hipótesis planteadas por los diversos autores,Mittal et al (2016) considera seis hipótesis: las cinco primeras afirman que cada una de las dimensiones de la que los tangibles se vinculan positivamente con la satisfacción del cliente y segundo mencionan que los tangibles se encuentran positivamente asociados con la lealtad del cliente, y así respectivamente con cada dimensión y con la variable tecnología, la hipótesis número 13 señala que la satisfacción del cliente pronostica la lealtad del cliente positivamente, y la última hipótesis se divide en seis sub hipótesis afirmado la primera que la unión de losMahmood et al, 2018). Por otro lado, cuatro de los autores consideran en sus hipótesis que existe una relación entre la calidad de servicio y la satisfacción del consumidor (Khan & Fasih, 2014; Siddiqi, 2011; Alafeshat & Alola, 2018; Mahmood et al, 2018).…”
unclassified